Antioxidant activity and selective cytotoxicity in HCT-116 and WI-38 cell lines of LC-MS/MS profiled extract from Capparis spinosa L - Oraibi, Amjad Ibrahim; Dawood, Ashour H.; Trabelsi, Ghada; Mahamat, Ousman B.; Chekir-Ghedira, Leila; Kilani-Jaziri, Soumaya (Frontiers in Chemistry, 2025)
IntroductionCapparis spinosa L. is significant among the family Capparidaceae for its survival and tolerance to dry environments. In this study, we evaluate the antioxidant and anticancer activities of extracts of roots and aerial parts of Capparis spinosa L.MethodsBioactive compounds, including phenolic acids and flavonoids, in various ethyl acetate fractions from the extracted roots and aerial parts, were identified using LC-MS/MS. Principal leaf constituents characterized included Rutin, Resveratrol, Astragalin, and others. The Rutin, Resveratrol, Astragalin, (of ethyl acetate fraction), leaves, and roots were screened for antioxidant activity using DPPH, FRAP, ABTS, and CUPRAC activity assays, as well as for cytotoxicity with the MTT assay.ResultThe antioxidant and anticancer activities of the samples were evaluated using DPPH, ABTS, FRAP, CUPRAC assays, and the MTT assay. Roots and Rutin consistently exhibited the strongest antioxidant activity across all assays, with Roots (IC50 = 0.06–0.36 mg/mL) excelling in FRAP and CUPRAC, and Rutin (IC50 = 0.013 mg/mL) showing the highest DPPH activity. In contrast, Astragalin displayed the weakest antioxidant potential. For anticancer activity, the MTT assay revealed that Leaves (IC50 = 23.26 μg/mL) and Roots (IC50 = 34.65 μg/mL) were the most potent against HCT-116 cells, outperforming Nutlin (IC50 = 62.72 μg/mL), with minimal toxicity to normal WI-38 cells. These results highlight the therapeutic potential of Roots and Rutin as strong antioxidant and anticancer agents.ConclusionThe results provide useful information concerning the medicinal potentials of Capparis spinosa L., particularly about HCT-116 and WI-38 cell line selectivity, and its relevance in the synthesis of natural antioxidants.